Restoration of HBV-specific CD8+ T-cell responses by sequential low-dose IL-2 treatment in non-responder patients after IFN-α therapy - Dongyao Wang (Nature Publishing Group, 2021)
Abstract Patients with chronic hepatitis B (CHB) undergoing interferon (IFN)-α-based therapies often exhibit a poor HBeAg serological response. Thus, there is an unmet need for new therapies aimed at CHB. This study comprised two clinical trials, including 130 CHB patients, who were treatment-naïve; in the first, 92 patients were systematically analyzed ex vivo for interleukin-2 receptor (IL-2R) expression and inhibitory molecules expression after receiving Peg-IFN-α-2b therapy. In our second clinical trial, 38 non-responder patients, in whom IFN-α therapy had failed, were treated with or without low-dose IL-2 for 24 weeks. We then examined the hepatitis B virus (HBV)-specific CD8+ T-cell response and the clinical outcome, in these patients. Although the majority of the participants undergoing Peg-IFN-α-2b therapy were non-responders, we observed a decrease in CD25 expression on their CD4+ T cells, suggesting that IFN-α therapy may provide a rationale for sequential IL-2 treatment without increasing regulatory T cells (Tregs). Following sequential therapy with IL-2, we demonstrated that the non-responders experienced a decrease in the numbers of Tregs and programmed cell death protein 1 (PD-1) expression. In addition, sequential IL-2 administration rescued effective immune function, involving signal transducer and activator of transcription 1 (STAT1) activation. Importantly, IL-2 therapy significantly increased the frequency and function of HBV-specific CD8+ T cells, which translated into improved clinical outcomes, including HBeAg seroconversion, among the non-responder CHB patients. Our findings suggest that sequential IL-2 therapy shows efficacy in rescuing immune function in non-responder patients with refractory CHB.